Perlindungan Hukum Pengguna Layanan Urunan Dana Melalui Penawaran Saham Berbasis Teknologi Informasi - Mamma, Suriyadi (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2020)
Abstract Crowdfunding services through information technology based stock offerings (equity crowdfunding) is an investment for people in the area of the industrial revolution 4.0 where companies that need capital can get funds, beside that people who have excess funds can use it by placing these funds in sectors that are be productive by using intermediaries called crowdfunding services providers. Problems regarding the protection of investor funds are often an important factor that supports the sustuinability of a bussiness beacuse of the factor of trust so that OJK regulates in aregulation concerning the protection of consumers in the financial services sectro. To maintain public trust, it is regulated regarding teh protection of investor funds against the actions of business actors. The organizer who manages the investor’s funds and distributes it to the issuer has an important role in equity crowdfunding so that teh responsibility is heavy as well, this is regulated in OJK regulations. The rsearch method used is normative with a statute approach by examining this principles in investment law with applicable laws and regulations. Regarding the protection of investor funds, basically this is regulated in OJK regulation Number 1/POJK.07/2013 which regulates consumer protection in the financial service sector against the behavior of business actorrs and this is strengthened by article 60 POJK Number 37 /2018 which imposes responsibility for losses on the organizer for the mistakes or negligence of the board of directors, employeses or parties who work with the oganizer. Keywords : equity crowdfunding, Investment, legal protection